2022
DOI: 10.1136/annrheumdis-2021-221754
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics analysis of rheumatoid arthritis yields sequence variants that have large effects on risk of the seropositive subset

Abstract: ObjectivesTo find causal genes for rheumatoid arthritis (RA) and its seropositive (RF and/or ACPA positive) and seronegative subsets.MethodsWe performed a genome-wide association study (GWAS) of 31 313 RA cases (68% seropositive) and ~1 million controls from Northwestern Europe. We searched for causal genes outside the HLA-locus through effect on coding, mRNA expression in several tissues and/or levels of plasma proteins (SomaScan) and did network analysis (Qiagen).ResultsWe found 25 sequence variants for RA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 51 publications
(90 reference statements)
1
27
0
Order By: Relevance
“…Selection of an appropriate b/tsDMARD is also critical for obtaining therapeutic effects at an early treatment course. In recent years, there have been increased reports on predicting optimal b/tsDMARDs using various technological platforms, such as machine learning and multi-omics analyses ( 30 33 ). Further studies are needed on the risk factors and treatment strategies for D2T RA, using genomic information and synovial tissue samples, with an in-depth consideration of the pathogenesis of the disease.…”
Section: Discussion: How To Prevent Patients From Becoming Difficult-...mentioning
confidence: 99%
“…Selection of an appropriate b/tsDMARD is also critical for obtaining therapeutic effects at an early treatment course. In recent years, there have been increased reports on predicting optimal b/tsDMARDs using various technological platforms, such as machine learning and multi-omics analyses ( 30 33 ). Further studies are needed on the risk factors and treatment strategies for D2T RA, using genomic information and synovial tissue samples, with an in-depth consideration of the pathogenesis of the disease.…”
Section: Discussion: How To Prevent Patients From Becoming Difficult-...mentioning
confidence: 99%
“…Genetic association estimates for seropositive and seronegative RA were taken from a published study of RA (21) that reported separate genome-wide association studies (GWAS) of seropositive (18,019 cases and 991,604 controls) and seronegative (8,515 cases and 1,015,471 controls) RA. One hundred and thirty-five autosomal single nucleotide polymorphisms (SNPs) that were associated with RA (either seropositive, seronegative or both) in previous GWAS of European ancestry or multi-ancestry were selected as IVs for RA (22).…”
Section: Methodsmentioning
confidence: 99%
“…The importance of non-HLA susceptibility loci was recently confirmed through analyses performed in large populations of patients with seropositive and seronegative RA. A genome-wide association study (GWAS) of 31 313 RA cases (68% seropositive) and ~1 million controls from Northwestern Europe found 25 sequence variants of the Janus Kinase (JAK)/ signal transducer and activator of transcription proteins (STAT) pathway characterising patients with RA, 33 for seropositive and 2 for seronegative (12). However, both signals in seronegative RA were also found in seropositive RA and pointed to causal genes: a missense variant rs2476601-A in PTPN22 and intronic variant rs7731626-A in ANKRD55.2 Another study, applying mendelian randomisation design on 3 GWASs metanalysis, found differences in cytokine patterns of genetic activity between seronegative and seropositive RA (13).…”
Section: Reviewmentioning
confidence: 99%